PRIVATE HOSPITAL CHOICES OF INFERTILE PATIENTS THAT RECIEVED IVF TREATMENT: A PILOT STUDY - Cengiz, Emrah; Ozsari, Haluk; Akyuz, Irfan; Tuzcuoglu, Ahmet; Hosgor, Haydar (European Scientific Journal, ESJ, 2015)
Reproduction and resuming the generation is one of the most important and basic instincts of all creatures. One of the biggest hurdles for the implementation of this instinct is infertility. The aim of this research is to determine the factors and the sources of information which are influential for women choosing IVF treatment in private hospitals, and to investigate the relationship between socioeconomic and demographic characteristics of the patients with these two variables. Main sample of the study is on 184 women who have received IVF treatment. Snowball sampling method was used as a sampling method. For women who have undergone IVF treatment the four most important factors that influence their choice of private hospitals, respectively; are hospital expertise in the field, the opportunity to be able to continue with the same physician during the treatment period, to be compelled and pregnancy success rates of the hospital. Four most important sources of information which are effective in applying to a hospital from the perspective of the patient, respectively; patients who had been treated in the hospital before, information offered to patients by the hospital, radio ads and a relative who works in a hospital.